The effect of folic acid intake on congenital anomalies. A systematic review and meta-analysis - Moges, Natnael; Sisay Chanie, Ermias; Anteneh, Rahel Mulatie; Zemene, Melkamu Aderajew; Gebeyehu, Asaye Alamneh; Belete, Melaku Ashagrie; Kebede, Natnael; Anley, Denekew Tenaw; Dessie, Anteneh Mengist; Alemayehu, Ermiyas; Dagnaw, Fentaw Teshome; Asmare, Zufan Alamrie; et al. (Frontiers in Pediatrics, 2024)
Background: Congenital anomalies pose a significant challenge to global health and result in considerable morbidity and mortality in early childhood. With the decline of other causes of death among children under five, the burden of congenital anomalies is expected to riseing, emphasizing the need for improved prenatal care, screening, and nutrition for pregnant women. This systematic review and meta-analysis aim to estimate the combined pooled effect of folic acid intake on congenital anomalies.To identify relevant research published up until December 30/2023, we conducted electronic searches of PubMed/Medline, PubMed Central, Hinary, Google, African Journals Online, Web of Science, Science Direct, and Google Scholar databases using predefined eligibility criteria. We used Excel to extract data and evaluated the studies using the JBI appraisal checklist.We computed the pooled effect size with 95% confidence intervals for maternal folic acid intake on congenital anomalies using STATA version 17 and the DerSimonian and Laird random effects meta-analysis model. We assessed statistical heterogeneity using Cochran's Q test, I2 statistic, and visual examination of the funnel plot.The review included 16 case-control, cohort, and cross-sectional studies. According to the results of this systematic review and meta-analysis, maternal folic acid intake significantly lowers the incidence of congenital anomalies (odds ratio (OR), 0.23; confidence interval (CI), 0.16, 0.32). Among the included studies, both the Cochrane Q test statistic (χ2 = 118.82, p <0.001) and I 2 test statistic (I 2 = 87.38%, p <0.001) revealed statistically significant heterogeneity. Egger's weighted regression (p <0.001) and funnel plot show evidence of publication bias in this metaanalysis.The results of the recent meta-analysis and systematic review have demonstrated a significant association between maternal folic acid intake and the risk of congenital anomalies. Specifically, children whose mothers received periconceptional folic acid supplementation had a 77% reduced risk of congenital anomalies. To further investigate the correlation between maternal folic acid supplementation and the occurrence of various congenital anomalies, particularly in developing countries, it is recommended that a comprehensive prospective study be conducted.